Understanding collective action - CGIAR Program on Collective Action and Property Rights (International Food Policy Research Institute, 2010)
Collective action can be understood as an action or series of actions taken by a group of individuals to achieve common interests. It can be voluntary for some or obligatory for others, such as compulsory membership in water users' associations. The efforts of hired or forced workers do not constitute collective action. While collective action is often considered the activities of formal organizations, many formal organizations exist on paper only and do not foster any real collective action. On the other hand, much collective action occurs informally through social networks or even through people coming together temporarily for specific purposes. Therefore, it can be an event (e.g. an organized march), a process (e.g. a series of participatory exercises), or an organization (e.g. microfinance group). Since members can act directly on their own or through an organization, collective action should not be equated with an organization.